Cyano-rich mesoporous carbon nitride nanospheres for visible-light-driven photocatalytic degradation of pollutants. Issue 12 (13th November 2018) - Chen, Chang-Bin; Li, Chen-Xuan; Zhang, Ying-Jie; Wang, Yun-Jie; Lu, Jia-Yuan; Liu, Hou-Qi; Li, Wen-Wei
Abstract : Visible-light-responsive photocatalysis offers exciting opportunities for sustainable environmental pollution control, but the unsatisfactory photoactivity of the existing photocatalysts impedes its practical application. Abstract : Visible-light-responsive photocatalysis offers exciting opportunities for sustainable environmental pollution control, but the unsatisfactory photoactivity of the existing photocatalysts impedes their practical application. Here, we fabricated a high-activity mesoporous carbon nitride nanosphere (MCNS) photocatalyst by a hard template synthesis method through incomplete polycondensation of the cyanamide precursors during thermal polymerization. The MCNS showed a unique nanosphere structure with a larger specific surface area and possessed more abundant cyano groups than two other graphitic carbon nitride (g-C3 N4 ) materials ( i.e., nanosheet and bulk g-C3 N4 ). Experimental results and theoretical calculations indicate important roles of the cyano groups in narrowing the catalyst band gap to favor visible light absorption and accelerating the separation of the electron–hole pairs. With such superior surface properties and improved charge separation efficiency, the MCNS exhibited 14.7 times higher photocatalytic activity for bisphenol A (BPA) degradation than the bulk g-C3 N4 . The MCNS also showed good stability during repeated use. Therefore, the as-prepared MCNS has great potential for visible-light-responsive photocatalysis in environmental remediation and other photocatalytic applications.